MiR-124 and the Underlying Therapeutic Promise of Neurodegenerative Disorders - Han, Dong; Dong, Xiaoyu; Zheng, Dongming; Nao, Jianfei (Frontiers in Pharmacology, 2020)
Neurodegenerative disorders (NDDs) are a group of chronic progressive neurological diseases based on primary neurodegeneration. The common pathological characteristics of various NDDs are neuronal degeneration, deletion, glial cell proliferation, and hypertrophy at specific locations in the nervous system. Proliferation and hypertrophy of microglia are manifestations of inflammation. MicroRNAs (miRNAs) have emerged as pivotal regulators of glial cells. MiRNAs are small non-coding molecules that regulate gene expression. Altered expression of miRNAs has been associated with several NDD pathological processes, among which regulation of the inflammatory response is key and a research hotspot at present. At the same time, miRNAs are also biological markers for diagnosis and potential targets for treating NDDs. MiR-124 is highly conserved and enriched in the mammalian brain. Emerging studies have suggested that miR-124 is closely related to the pathogenesis of NDDs and may be a viable therapeutic strategy to reduce inflammation associated with NDDs. In this review, we describe an overview of general miRNA biology, implications in pathophysiology, the potential roles of miR-124 associated with inflammation, and the use of miRNA as a future biomarker and an application for NDD therapy.